Conflict Resolution in the Performance of Collaborative Governance: A Systematic Literature Review - Tando, Cahyoko Edi; Sudarmo, Sudarmo; Haryanti, Rina Herlina (Jurnal Ilmiah Peuradeun, 2021)
Conflict is one of the problems that occurs when every human, organization, and the social life of the organization. Conflict can be reviewed through the root of existing problems that can be internal or can be external. The science of public administration has the right resolution in dealing with the mechanism of collaborative governance. The literature review approach applied was based on scientific journals published in the database. The database that the authors used were Scopus, Science Direct, and Taylor and Francis Group. The result of this research showed that the implementation of the proposed collaborative governance form of cooperation structure and the policy then is the creation of the community plan making. Furthermore, the types of conflicts resolved by collaborative governance in the 2015-2019 period were the source of conflicts that often occur in that period. Researchers suggested that researching collaborative governance can be developed in government so that it can be implemented in overcoming various public problems.